Brief EcoMeditation Associated With Psychological Improvements: A Preliminary Study - Dawson Church PhD; Peta Stapleton PhD; Debbie Sabot PsychSc (SAGE Publishing, 2020)
Background A growing body of clinical research attests to the psychological and physiological benefits of meditation. EcoMeditation is a non-pharmacological therapeutic approach used to promote health and well-being, comprising four evidence-based techniques: The Quick Coherence Technique for regulating heart rate variability (HRV), Emotional Freedom Techniques (EFT), mindfulness, and neurofeedback. Objectives This study investigated changes in psychological symptoms of anxiety, depression, posttraumatic stress disorder (PTSD), pain, and happiness following a one-day EcoMeditation training workshop delivered in a large-group format and at 3-months post-intervention. Methods A convenience sample of 208 participants (137 women, 71 men) aged between 21 and 87 years ( M  = 55.4 years; SD  = 12.8 years) attended a one-day EcoMeditation training workshop. Participants completed a pen-and-paper survey pre-workshop and post-workshop, and an online survey three months following the EcoMeditation intervention. Results Post-workshop results revealed significant reductions in anxiety (−23.4%, p  <   .001), depression (−15.8%, p  =   .011), PTSD (−11.8%, p  <   .001), and pain (−18.5%, p  <   .001), while happiness scores increased significantly (+8.9%, p  <   .001). At 3-month follow-up, one-way repeated-measures ANOVA ( N  =   65) found significant decreases in anxiety between pre-test and post-test, and pain between pre-intervention and 3-month follow-up. Differences in depression and PTSD scores were not significant over time. Happiness scores significantly increased from pre-test to 3-month follow-up. However, post-hoc analyses suggested that the final sample size was inadequate to detect significant differences between time points. Conclusion Findings provide preliminary support for EcoMeditation as a brief group-based stress reduction intervention with benefits for improved psychological functioning.